circARF3 Alleviates Mitophagy-Mediated Inflammation by Targeting miR-103/TRAF3 in Mouse Adipose Tissue - Zhenzhen Zhang; Tiantian Zhang; Ruonan Feng; Hongtao Huang; Tianyu Xia; Chao Sun (Elsevier, 2019)
Adipose inflammation is an important cause for obesity-associated metabolic disorders, including insulin resistance and hypertension. Here we investigated that a circular RNA (circRNA), which we termed circARF3 (ADP-ribosylation factor 3), acts as an endogenous miR-103 sponge to alleviate adipose inflammation by promoting mitophagy. On the other hand, miR-103 aggravated inflammation by inhibiting mitophagy, revealing that miR-103 acts as a positive regulator of adipose inflammation. Furthermore, we found that tumor necrosis factor receptor-associated factor 3 (TRAF3), as a miR-103 downstream target, mediates the functions of miR-103 in adipose inflammation. Overexpressing TRAF3 attenuated miR-103-induced inflammation by accelerating mitophagy. Moreover, we identified that circARF3 blocked miR-103 effects, which resulted in an increase in TRAF3 expression. TRAF3 restrained the nuclear factor κB (NF-κB)-signaling pathway, heightened mitophagy, and suppressed NLRP3 inflammasome activation ultimately. Our data showed that circARF3 acts as an endogenous miR-103 sponge to inhibit mitophagy-mediated adipose inflammation both in vitro and in vivo. These findings disclose a new regulatory pathway for adipose inflammation, which consists of circARF3, miR-103, and TRAF3. This study can be a useful addition to our knowledge, as it provides a new strategy for the prevention of adipose inflammation in obesity disorder. Keywords: circRNA, miR-103, TRAF3, mitophagy, inflammation, adipose tissue